Optic Nerve Degeneration after Retinal Ischemia/Reperfusion in a Rodent Model - Renner, Marina; Stute, Gesa; Alzureiqi, Mohammad; Reinhard, Jacqueline; Wiemann, Susanne; Schmid, Heiko; Faissner, Andreas; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2017)
Retinal ischemia is a common pathomechanism in many ocular disorders such as age-related macular degeneration, diabetic retinopathy, glaucoma or retinal vascular occlusion. Several studies demonstrated that ischemia/reperfusion leads to morphological and functional changes of different retinal cell types. However, little is known about the ischemic effects on the optic nerve. The goal of this study was to evaluate these effects. Ischemia was induced by raising the intraocular pressure in one eye of rats to 140 mmHg for 1 hour followed by natural reperfusion. After 21 days, histological as well as qRT-PCR analyses of optic nerves were performed. Ischemic optic nerves showed an infiltration of cells and also degeneration with signs of demyelination. Furthermore, a migration and an activation of microglia could be observed histologically as well as on mRNA level. In regard to macroglia, a trend toward gliosis could be noted after ischemia induction by vimentin staining. Additionally, an up-regulation of GFAP mRNA was found in ischemic optic nerves. Counting of Olig2+ cells revealed a decrease of oligodendrocytes in the ischemic group. Also, MBP and MOG mRNA expression was down-regulated after induction of ischemia/reperfusion. On immunohistological level, a decrease of MOG was detectable in ischemic optic nerves as well. In addition, SMI-32 stained neurofilaments of longitudinal optic nerve sections showed a strong structural damage of the ischemic optic nerves in comparison to controls. Consequently, retinal ischemia impacts optic nerve degeneration. These findings could help to better understand the course of destruction in the optic nerve after an ischemic insult. Especially for therapeutic studies, the optic nerve is important because of its susceptibility to be damaged as a result to retinal ischemic injury and also its connecting function between the eye and the brain. So, future drug screenings should target not only the retina, but also the functionality and structure of the optic nerve. In the future, these results could lead to the development of new therapeutic strategies for treatment of ischemic injury.